Allometry of individual reproduction and defense in eusocial colonies: A comparative approach to trade-offs in social sponge-dwelling Synalpheus shrimps. - Sarah L Bornbusch; Jonathan S Lefcheck; J Emmett Duffy (PLoS ONE, 2018)
Eusociality, one of the most complex forms of social organization, is thought to have evolved in several animal clades in response to competition for resources and reproductive opportunities. Several species of snapping shrimp in the genus Synalpheus, the only marine organisms known to exhibit eusociality, form colonies characterized by high reproductive skew, and aggressive territoriality coupled with cooperative defense. In eusocial Synalpheus colonies, individual reproduction is limited to female 'queens', whose fecundity dictates colony growth. Given that individual reproduction and defense are both energetically costly, individual and colony fitness likely depend on the optimal allocation of resources by these reproducing individuals towards these potentially competing demands. Synalpheus species, however, display varying degrees of eusociality, suggesting that reproducing females have adopted different strategies for allocation among reproduction and defense. Here, we use structural equation modeling to characterize the relationships between the allometry of queen reproductive capacity and defensive weaponry, and colony size in six eusocial Synalpheus species, estimating trade-offs between reproduction and defense. We document strong trade-offs between mass of the fighting claw (defense) and egg number (reproduction) in queens from weakly eusocial species, while the trade-off is reduced or absent in those from strongly eusocial species. These results suggest that in less cooperative species, intra-colony conflict selects for queen retention of weapons that have significant costs to fecundity, while reproducing females from highly eusocial species, i.e., those with a single queen, have been able to reduce the cost of weapons as a result of protection by other colony members.